An assessment of the reliability and validity of job performance measurement - Johanim Johari; Khulida Kirana Yahya (Penerbit Universiti Kebangsaan Malaysia, 2012)

(untitled)
This study examines the psychometric properties of the job performance construct by espousing task performance and organizational citizenship behavior (ocB) items. The latter comprises of sportsmanship, civic virtue, courtesy, altruism, conscientiousness, and innovative behavior An a priori proposition is made that the job performance measurement could be explained by two factors: task performance and OCB. The findings support the hypothesis that job performance can be measured by the two hypothesizedfactors. However, four factors ofOCB, i.e. civic virtue, sportsmanship, conscientiousness, and courtesy, load on the task performance factor, while altruism and innovative behavior load on the OCB construct. The results provide evidence of construct reliability and validity of the job performance items, indicating that the instrument is suitable for Malaysian studies. Implications of the findings and recommendations are also discussed.